Eksistensi Moderasi Islam dalam Kurikulum Pembelajaran PAI di SMA - Yunus, Yunus; Salim, Arhanuddin (Universitas Islam Negeri Raden Intan Lampung, 2018)
Students become very vulnerable groups dragged down by the flow of religious radicalism. The age is still very young and still unstable with a burning spirit, and longing to practice religion more kāffah (comprehensive) making young groups including Muslim students in high school will be the most vulnerable social groups infiltrated and targeted by radical groups preach religious understanding and attitudes that are rigid and tend to be superficial. On the other hand, religious liberalism at the same time has also begun to infiltrate some young people, including Muslim students in high school. So it is necessary, a strategy to instill moderate Islamic values into students by utilizing the teaching and learning activities of Islamic Education in the classroom. This is because the main actors who are perpetrators of violence, anarchistic actions in religious conflict with religious backgrounds are groups affiliated to Islam. So that inevitably, Islamic Education has moral and social responsibility to help find a way out.